2019
DOI: 10.3390/s19071555
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Wearable Sensors for Joint Angle Estimation: A Systematic Review

Abstract: Motion capture systems are recognized as the gold standard for joint angle calculation. However, studies using these systems are restricted to laboratory settings for technical reasons, which may lead to findings that are not representative of real-life context. Recently developed commercial and home-made inertial measurement sensors (M/IMU) are potentially good alternatives to the laboratory-based systems, and recent technology improvements required a synthesis of the current evidence. The aim of this systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
203
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(226 citation statements)
references
References 69 publications
22
203
1
Order By: Relevance
“…Results in Table III showed that the quality of angle measurement decreases while the treadmill walking speed increases. This is consistent with results in previous studies (reviewed in [41]). Skin tissue artefact (STA) is a major source of RMSE by applying additional noise to the bodyworn sensors [42].…”
Section: Accuracy Of Ankle Angle Measurementsupporting
confidence: 94%
“…Results in Table III showed that the quality of angle measurement decreases while the treadmill walking speed increases. This is consistent with results in previous studies (reviewed in [41]). Skin tissue artefact (STA) is a major source of RMSE by applying additional noise to the bodyworn sensors [42].…”
Section: Accuracy Of Ankle Angle Measurementsupporting
confidence: 94%
“…For functional calibration movements 4a, 4b, and 4c, the second axis was defined as the principal acceleration axis through a PCA on accelerometer signals transformed in a lab-fixed reference frame. The 3D orientation of the pelvis and joint angles for the hips, knees, and ankles were calculated from the segment orientations based on the recommendations of the International Society of Biomechanics [6] for the different functional calibration movements. Flexion-extension were rotations around the X axis, abduction-adduction was around the Y axis, and internal-external rotations were around the Z axis.…”
Section: Signal Processingmentioning
confidence: 99%
“…Although they generally contain a 3D accelerometer, a 3D gyroscope, and an optional 3D magnetometer, an IMU does not measure joint angles perfectly. Joint angles obtained via signal integration typically drift over time [4,5] and their accuracy varies with the joint assessed and the movement complexity [6,7]. While an error under 5 • is generally accepted for most clinical gait applications [8], the measurement error typically ranges from 5 • to 18.8 • depending on the joint and the plane of motion [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further way to estimate the pose of the human body consists in using Micro Electro-Mechanical Systems (MEMS), such as Magnetic, Angular Rate, and Gravity (MARG) sensors, including triaxial gyroscopes, accelerometers, and magnetometers [10], [11]. These sensors can be easily integrated with wearable devices and can be used to reconstruct the pose of the human body through specific algorithms [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%